(untitled) (Patrimônio e Memória, 2011)
This paper examines the evolution of the comic as the modification of the painful transition from medieval to modern thought. The highest expression of the comic, in the medieval period, lies in the popular parties, universal space of destruction and regeneration of its own dynamism of social reality. But in the medieval period, the universal character of the comic and laughter prevailed, the same does not happen within modernity, when the laughter becomes serious and focused on discrete objects, undergoing transformations in the way of their expression, namely in everyday and on days of festivity. These changes raise some questions: what were the reasons for a change and the process engendered in the way of thinking and experiencing everyday life? What is the space given to the comic, laughter seen as serious? The unspeakable’s, own perception of changes and crises, which found its expression in voices?